Development of a Data Reduction Algorithm for Optical Wide Field Patrol (OWL) II: Improving Measurement of Lengths of Detected Streaks - Sun-Youp Park; Jin Choi; Dong-Goo Roh; Maru Park; Jung Hyun Jo; Hong-Suh Yim; Young-Sik Park; Young-Ho Bae; Jang-Hyun Park; Hong-Kyu Moon; Young-Jun Choi; Sungki Cho; et al. (Journal of Astronomy and Space Sciences, 2016)
As described in the previous paper (Park et al. 2013), the detector subsystem of optical wide-field patrol (OWL) provides many observational data points of a single artificial satellite or space debris in the form of small streaks, using a chopper system and a time tagger. The position and the corresponding time data are matched assuming that the length of a streak on the CCD frame is proportional to the time duration of the exposure during which the chopper blades do not obscure the CCD window. In the previous study, however, the length was measured using the diagonal of the rectangle of the image area containing the streak; the results were quite ambiguous and inaccurate, allowing possible matching error of positions and time data. Furthermore, because only one (position, time) data point is created from one streak, the efficiency of the observation decreases. To define the length of a streak correctly, it is important to locate the endpoints of a streak. In this paper, a method using a differential convolution mask pattern is tested. This method can be used to obtain the positions where the pixel values are changed sharply. These endpoints can be regarded as directly detected positional data, and the number of data points is doubled by this result.